Amiodarone-induced neuromyopathy in a geriatric patient. Issue 11 (4th November 2020) - Stanton, Michael Mark; Samii, Leyla; Leung, Gentson; Pearce, Paula
Abstract : Amiodarone is an antiarrhythmic medication with many side effects. Neuromyopathy is a rare adverse effect. We present an 87-year-old woman with bilateral leg pain and weakness in the context of amiodarone. She was admitted to the Acute Geriatric Unit in Calgary, Alberta, Canada. On examination, hip flexor and extensor strength were 2/5 bilaterally while knee flexor and extensor strength were 4/5 and 3/5, respectively. Creatine kinase and C-reactive protein levels were normal. MRI of the lumbar spine showed mild central canal stenosis. Electromyography and nerve conduction testing showed a severe axonal length-dependent polyneuropathy of the left lower extremity. There was evidence of myopathic changes to the left iliopsoas muscle. Overall, a neuromyopathic process affecting the lower extremities was supported. After discontinuation of amiodarone, mobility and function significantly improved. Although a rare complication of amiodarone, neuromyopathy should be considered in patients with compatible symptomatology.